USING KAHOOT WEBSITE IN LEARNING GRAMMAR: Pre-experimental Research - Musdalifah; Abdul, Nurdevi Bte; Saiful (FKIP Unismuh Makassar, 2018)
The research aimed to find out the improvement of the students’ learning grammar by using Kahoot website. The research applied pre-experimental research with one group pre-test and post-test. The researcher used purposive sampling technique.The sample of the research was class X MIPA 2 of SMAN 8 Gowa in academic year 2018/2019 which consisted of 37 students. The researcher used simple present and past tense of reading test as instrument in pre-test and post-test. The research findings indicated that Kahoot website can improve students’ Learning grammar. It was proved by the mean score of pre-test in present tense was 56.86it classified as fair, posttest was 73.72,it classified as good and the improvement of pretest to be posttest was 29.65%. In addition, the mean score of pretest in Past Tense was 51.89 that classified as poor, posttest was 70.81 that classified as fair good and the improvement of pretest to posttest was 36.46%. Therefore, there was the improvement of the students’ grammar in terms of simple present and past tense. The result of improvement is also proved with t-test value. The researcher found that the value of t-test (4.543) was greater than t-table (1.687). this value means that there was significantly difference between the result of the students’ pre-test and post test. It was concluded that the use of Kahoot website can improve students’ learning grammar at the First Grade of SMAN 8 Gowa.